The influence of cutting mode elements on the technological parameters of the process of milling blanks of titanium alloy thin-walled parts - Aleksandr N. Unyanin; Aleksandr V. Chudnov (Frontier Materials & Technologies, 2024)
The purpose of a rational mechanical processing mode remains an urgent task of pre-production engineering. Known recommendations and methods for selecting this mode are focused on the processing of solid blanks and do not take into account the fact that when processing thin-walled blanks, the temperatures in the processing zone and the surface layer of the blank differ. The study is aimed at identifying patterns in changing the parameters of the milling process of thin-walled blanks depending on the mode elements, as well as developing recommendations for selecting this mode. The authors performed numerical simulation of technological parameters of the milling process of solid and thin-walled blanks made of titanium alloy under various modes. The cutting speed, cutting depth and feed per cutter tooth were varied. The cutting force, power and densities of heat sources and the temperature in the surface layer of the blank, in the contact zones of the cutter tooth with the blank and the chips with the front surface of the tooth were calculated. It has been found that when milling thin-walled blanks, the temperature field differs significantly from that formed when processing solid blanks due to low heat removal from the unprocessed surface. Increasing the feed per tooth by 45 % leads to an insignificant decrease in temperatures in the cutting zone (by 5...12 %). Increasing the cutting speed by 25 %, on the contrary, leads to an increase in temperatures by 5...10 %. Increasing the cutting depth leads to an increase in the temperature in the chip-tooth contact zone by 1.5 times and to an increase in the temperature in the tooth-blank contact zone.